Business Cycles in Developed and Emerging Economies: Evidence from a Univariate Markov Switching Approach - Altug, Sumru; Bildirici, Melike (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2012)
This paper characterizes business cycle phenomena in a sample of twenty-seven developed and emerging economies using a univariate Markov regime-switching approach. It examines the efficacy of this approach for detecting business cycle turning points and for identifying distinct economic regimes for each country in question. The paper also presents results on business cycle synchronization for the sample of countries under consideration. The findings of the paper have implications for understanding the commonalities and differences in cyclical phenomena for a diverse set of developed and emerging economies.
Keywords: business cycles; Markov switching approach; nonparametric modeling; turning point analysis; TIME-SERIES; Business & Economics; International Relations